A randomized control trial of a behavioral intervention for older adults with subjective cognitive complaints that combines cognitive rehabilitation strategies and lifestyle modifications. Issue 1 (2nd January 2023) - Denny, Katherine G.; Chan, Michelle L.; Gravano, Jason; Harvey, Danielle; Meyer, Oanh L.; Huss, Olivia; Farias, Sarah Tomaszewski
ABSTRACT: This study examined the effectiveness of a 10-week cognitive rehabilitation and lifestyle modifying intervention that integrated compensation strategies, engagement in brain activities, and improving everyday function. The trial was registered with ClinicalTrials.gov (NCT03549078). Older adults with subjective cognitive concerns and normal performance on a cognitive screener were randomized into the intervention (n = 28) or waitlist control (n = 29) groups. The total sample comprised 57 individuals (age, mean = 74.8, SD = 6.5), mostly female (80.4% of the total sample), and well educated (education years: mean = 15.9, SD = 2.1). Outcome measures were completed at baseline, and immediately and 3- and 6-months post-intervention. Intervention participants reported significant improvements in aspects of everyday functioning and select compensation strategies and brain health activities. Increased compensation strategy use was maintained at 6-month follow up. This intervention has benefits for improving everyday functioning and increasing engagement with compensation strategies and brain health activities.